Science, Power, and Legitimacy: The Political Role of Rulers in the Dynamics of the Development of Science in the Classical Islamic World (Abbasid–Andalusian) - Indah, Fitriana; Choirunnisak , Choirunnisak; Yusman, Yusman; Arifin, Faizal Muhammad; Ashani, Salahuddin (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
The development of science in the classical Islamic world was not only organic. Still, it was also shaped by power relations that made science a means of political legitimacy and social control. A research gap arises from the lack of studies that explicitly highlight how political patronage not only supported but also framed science’s epistemological direction and institutionalization. This study aims to specifically identify the political mechanisms by which rulers influence the production, authority, and institutionalization of science, and examine their implications for the formation of power legitimacy. A qualitative historical-analytical approach is employed by analyzing primary sources, including chronicles and documents from scientific institutions, as well as contemporary secondary literature that discusses the patronage of science in the Abbasid, Fatimid, and Andalusian periods. The results reveal three main mechanisms of ruler intervention. First, financial and symbolic patronage of scholars and scientists created intellectual authority and strengthened claims to power. Second, the institutionalization of science was facilitated through the establishment of the Bayt al-Ḥikmah, the Nizamiyyah madrasah, and the University of Córdoba, which became centers of knowledge production, curation, and dissemination. Third, cultural diplomacy facilitated the transfer of knowledge from Greek, Persian, Indian, and Arabic traditions, leading to intellectual transformation across civilizations. In conclusion, the relationship between knowledge and power during the classical Islamic period not only enriched intellectual traditions but also became a hegemonic instrument that strengthened political legitimacy through scientific authority directed toward social welfare and the construction of a universal civilization.